Characterization of Visual Pathway Abnormalities in Infants With Congenital Zika Syndrome Using Computed Tomography and Magnetic Resonance Imaging. Issue 4 (December 2021) - Henderson, Amanda D.; Ventura, Camila V.; Huisman, Thierry A. G. M.; Meoded, Avner; Hazin, Adriano N.; van der Linden, Vanessa; de Lima Petribu, Natacha C.; May, William N.
Abstract : Background: Severe visual impairment is present in nearly all infants with congenital Zika syndrome (CZS); however, ocular abnormalities are present only in a subset of these infants. The purpose of this study was to characterize the visual pathway abnormalities seen on computed tomography (CT) and MRI scans in infants with CZS. Methods: Preliminary neuroimaging information was obtained from a referred sample of 105 infants with clinical and epidemiologic data consistent with CZS in the Pernambuco state of Brazil. Subjects were excluded if Zika virus infection was not confirmed by serologic or cerebrospinal fluid studies or if images were nondiagnostic. Of the 105 subjects initially screened, head CT images adequate for interpretation were available for 54, and brain MRI images adequate for interpretation were available for 20. Four patients had both CT and MRI images. Magnetic resonance imaging and CT scans from infants with CZS were systematically reviewed for globe malformations, optic nerve and chiasmal atrophy, occipital cortical volume loss, white matter abnormalities, ventriculomegaly, and calcifications. Neuroimaging findings were correlated with measures of visual function and with ocular examinations in these infants. Results: Thirty-three males and 37 females were included in the analysis. The mean age of the infants at the time of neuroimaging was 16.0 weeks (range 0 days–15.5 months), and the mean gestational age at the time of birth was 38 weeks. All patients were from the Pernambuco state of Brazil. Overall, 70 of 74 (95%) scans showed occipital volume loss, whereas 9 (12%) showed optic nerve atrophy, 3 (4%) showed chiasmal atrophy, and 1 (1%) showed an ocular calcification. Sixty-two of the infants underwent ophthalmologic examinations. A total of 34 (55%) infants had at least one documented structural ocular abnormality, and 26 (42%) had at least one structural ocular abnormality documented in both eyes. Of those with available visual acuity data, all had visual impairment. Among those with visual impairment and normal eye examinations, 100% had visual pathway abnormalities on neuroimaging, including 100% with occipital cortical volume loss, 8% with optic nerve atrophy, and 8% with chiasmal atrophy. Conclusion: Our results suggest that cortical visual impairment related to structural abnormalities of the occipital cortex is likely an important cause of visual impairment in children with CZS with normal eye examinations.